The Effect Of Swap Line Establishment To Developing Countries Portfolio Flows In Subprime Mortgage Crisis - Murharsito Murharsito (Media Ekonomi dan Manajemen, 2014)
Abstract This paper tries to investigate the effect of swap line establishment to the portfolio flows to developing countries in the subprime mortgage crisis. This issue is interesting to investigate because the swap line establishment is relatively new phenomenon in the international financial resolution. It also involve major economic powers as the partner of developing countries in this arrangement. Sample of this research consist of 64 developing countries and the observation period year is 2009. The quantitative approach specifically regression analysis is chosen to obtain the result.  From the analysis result reveals that the swap presence has no effect to the portfolio flows to the developing and emerging market. The swap partner statistical result is more convincing; but the relationship is weak it is significant at the alpha 10 %. And finally the swap amount provide much better result, it has the highest relationship significant at the alpha of 1 % with the portfolio flows to developing countries. Keywords : swap line, portfolio flows, developing countries, subprime mortgage crisis Abstraksi           Tulisan ini mencoba untuk menganalisis pengaruh dari pembentukan jalur swap terhadap arus portofolio menuju negara berkembang dalam krisis subprime mortgage. Isu ini menarik untuk dipelajari karena pembentukan jalur swap adalah fenomena yang relatif baru dalam penyelesaian permasalahan keuangan internasional. Hal ini juga melibatkan kekuatan-kekuatan ekonomi besar sebagai partner dari negara-negara berkembang dalam perjanjian ini. Sampel dalam penelitian ini terdiri dari 64 negara berkembang dan periode pengamatan adalah tahun 2009. Pendekatan kuantitatif secara lebih spesifik yaitu analisis regresi dipilih untuk mendapatkan hasil perhitungan. Dari hasil perhitungan mengungkapkan bahwa pembentukan swap tidak memiliki pengaruh terhadap arus portofolio ke negara berkembang. Hasil statistik dari swap partner lebih meyakinkan, walaupun hubungannya lemah signifikan pada alpha 10 %. Dan terakhir nilai swap memberikan hasil yang lebih baik, memiliki hubungan yang lebih erat signifikan pada alpha 1 % dengan aliran modal menuju negara berkembang. Kata kunci : jalur swap, arus portofolio, negara berkembang, krisis subprime mortgage